Art. 348 of the 1984 Civil Code or superstition of the divorce - De Valdivia Cano, Ramiro (2015)
The title of this essay refers primarily to the positive rule governing the institution of divorce in Peru: the art. 348 of the Civil Code. This rule is widely developed in the Code and subsequent laws have being expanded the scope to include causal divorce that contradicts logic and common sense. Besides, it refers to what Gilbert K. Chesterton called “superstition divorce”: the perverse argument that states divorce is the panacea for all problems in family relationships. The author argues that for reasons of legal, ethical, social, political and anthropological  nature, the state and society are obliged to promote and defend marriage and the family; and the indissoluble character of marriage.